Application of a didactic sequence: the collaborative scientific doing for the teaching of chemistry in basic education - Medeiros, Maria Salome Ramos (Seven Editora, 2023)
This article is the result of research that focused on the study of scientific work with collaborative proposals and as a field of study, "Chemistry and Kitchen". In this way, we sought to dynamize the teaching-learning process of Chemistry, establishing the School as an ideal space for stimulating scientific research and building a fair, democratic, and inclusive society, based on everyday practical activities. The research was divided into the following steps: bibliographic review for the formation of a database on the subject under study, followed by the application of a didactic sequence with collaborative proposals for second and third-year high school students of the Technical course in Agroecology of a school of the state education network, in a small town in the interior of Bahia,  in the year 2021. After the application of the didactic sequence, in possession of the data, the analysis was carried out, finally presenting the results of the research. It is worth mentioning that, during an asynchronous period, scientific research relied on the help of some digital tools, such as online laboratories and their potential, for the beginning of practical activities in the discipline of Chemistry in High School. DOI: https://doi.org/10.56238/thebestiimulti2022-009